«We need more women in managerial jobs» – Gender equality and management in the Nordic context : Deconstruction and critical perspectives - Tienari, Janne (2016)
Focusing on the Nordic context, this article highlights complexities between gender equality discourse established at the societal level and discursive practice in organizations, particularly in relation to management, managing and managers. This research task is carried out by deconstructing a management text, and grounding the deconstruction in critical feminist literature. This analysis illustrates how managerial discourse is challenged and questioned by pro-egaliterian arguments in the Nordic context. However, it also demonstrates the pervasiveness of the gendered elements in managerial discourse, which relies on specific conceptions of parenthood where motherhood is constructed as problematic whereas fatherhood remains absent – and thus unproblematic. It is suggested that the ‘Nordic case’ provides a fruitful basis for similar studies in other societal contexts in Europe.